+0  
 
0
378
1
avatar

(¬p V ¬q V r) → ¬ (q V r)

 Sep 21, 2017
 #1
avatar+21295 
+2

Simplify the following logical expression using the Laws of Logic.

 

(¬p ∨ ¬q V r) → ¬ (q ∨ r) = ¬r ∧ ( p ∨ ¬q )

 

 

 

laugh

 Sep 22, 2017

37 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.